T'ai chi & aikido - Popovic, Andrew (Lorenz Books, 2007)
Clearly illustrated with more than 700 photographs, the step-by-step guides to the basic postures, movements, techniques and applications of Tai Chi and Aikido are demonstrated by expert practitioners. This book will prove a useful reference tool time and time again, as the key to enjoyment and progression is the practice of the basic skills described in these pages. With advice on choosing schools and useful contacts, this book allows the reader to fully discover both disciplines and choose the methods that are right for their lifestyle and needs.